High-throughput expression of animal venom toxins in Escherichia coli to generate a large library of oxidized disulphide-reticulated peptides for drug discovery. Issue 1 (December 2017) - Turchetto, Jeremy; Sequeira, Ana; Ramond, Laurie; Peysson, Fanny; Brás, Joana; Saez, Natalie; Duhoo, Yoan; Blémont, Marilyne; Guerreiro, Catarina; Quinton, Loic; Pauw, Edwin; Gilles, Nicolas; et al.
Abstract Background Animal venoms are complex molecular cocktails containing a wide range of biologically active disulphide-reticulated peptides that target, with high selectivity and efficacy, a variety of membrane receptors. Disulphide-reticulated peptides have evolved to display improved specificity, low immunogenicity and to show much higher resistance to degradation than linear peptides. These properties make venom peptides attractive candidates for drug development. However, recombinant expression of reticulated peptides containing disulphide bonds is challenging, especially when associated with the production of large libraries of bioactive molecules for drug screening. To date, as an alternative to artificial synthetic chemical libraries, no comprehensive recombinant libraries of natural venom peptides are accessible for high-throughput screening to identify novel therapeutics. Results In the accompanying paper an efficient system for the expression and purification of oxidized disulphide-reticulated venom peptides inEscherichia coli is described. Here we report the development of a high-throughput automated platform, that could be adapted to the production of other families, to generate the largest ever library of recombinant venom peptides. The peptides were produced in the periplasm ofE. coli using redox-active DsbC as a fusion tag, thus allowing the efficient formation of correctly folded disulphide bridges. TEV protease was used to remove fusion tags and recover the animal venom peptides in the native state. Globally, within nine months, out of a total of 4992 synthetic genes encoding a representative diversity of venom peptides, a library containing 2736 recombinant disulphide-reticulated peptides was generated. The data revealed that the animal venom peptides produced in the bacterial host were natively folded and, thus, are putatively biologically active. Conclusions Overall this study reveals that high-throughput expression of animal venom peptides inE. coli can generate large libraries of recombinant disulphide-reticulated peptides of remarkable interest for drug discovery programs.